2013
DOI: 10.1093/humrep/det059
|View full text |Cite
|
Sign up to set email alerts
|

Growth retardation in human blastocysts increases the incidence of abnormal spindles and decreases implantation potential after vitrification

Abstract: This study provided new insights into the possible implications of abnormalities in spindle formation in growth-retarded human blastocysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 30 publications
2
38
0
1
Order By: Relevance
“…Our data parallels these reports; however, these present data also suggest that even those embryos that are diagnosed as euploid can develop to the blastocyst stage at varying rates, suggesting that other factors aside from chromosomes influence growth. For example, mitochondrial, spindle abnormalities, and specific gene expression have all been shown to influence embryo development (Hashimoto et al, 2013;Hsieh et al, 2004;Wood et al, 2007). The use of assisted hatching may confound our data, causing embryos to artificially blastulate prematurely.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our data parallels these reports; however, these present data also suggest that even those embryos that are diagnosed as euploid can develop to the blastocyst stage at varying rates, suggesting that other factors aside from chromosomes influence growth. For example, mitochondrial, spindle abnormalities, and specific gene expression have all been shown to influence embryo development (Hashimoto et al, 2013;Hsieh et al, 2004;Wood et al, 2007). The use of assisted hatching may confound our data, causing embryos to artificially blastulate prematurely.…”
Section: Discussionmentioning
confidence: 94%
“…Campbell et al (2013a;2013b) used a time-lapse culture system to show that aneuploid blastocysts were slower to blastulate compared with euploid blastocysts. The lower pregnancy and implantation rates associated with day 6 blastocysts could be attributed to spindle abnormalities, mitochondrial deficiencies or gene expression (Hashimoto et al, 2013;Hsieh et al, 2004;Shapiro et al, 2013;Wood et al, 2007). These deficiencies could affect the blastocysts' ability to implant and develop in-utero.…”
Section: Introductionmentioning
confidence: 99%
“…The final inclusion was 13 studies that met the selection criteria for our meta‐analysis. Hence, 23 studies were included in the following meta‐analyses . The main characteristics and assessment for risk of bias of the included studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…In line with this, we observed that transfer of euploid day 5 blastocyst resulted in higher implantation and live birth rate than the transfer of euploid day 6 blastocyst, while there was no significant difference between day 5 and day 6 blastocyst transfers for clinical pregnancy and ongoing pregnancy rates. Recent studies have found that intracellular factors, including spindle assembly checkpoints, abnormal spindles, microtubule kinetics, and mitochondrial function, can cause developmental delay in preimplantation embryo. The impact of intracellular factors on the euploid embryos may be a reason for the higher pregnancy rate of day 5 blastocyst transfer than day 6 blastocyst transfer …”
Section: Discussionmentioning
confidence: 99%
“…The endometrium was prepared by administration of GnRH agonist (600 μg/day, Suprecur® nasal solution 0.15 %; Mochida Pharmaceutical; Tokyo, Japan) for 3 weeks followed by increasing doses of oral estradiol valerate (Progynova®; Bayer Schering Pharma; Zürich, Switzerland) from 1 to 4 mg for 2 weeks [30]. After ultrasonographical confirmation that the endometrium was thicker than 8 mm, chlormadinone acetate (Lutoral®; Shionogi & Co.; Osaka, Japan) was administered (6 mg/day).…”
Section: Preparation Of the Endometriummentioning
confidence: 99%